Effect of the fibre length on the mechanical anisotropy of glass fibre–reinforced polymer composites printed by Multi Jet Fusion - Liu, Xiaojiang (2022)
Mechanical anisotropy greatly influences the applications of materials printed by additive manufacturing techniques such as Multi Jet Fusion (MJF) and selective laser sintering. However, the mechanical anisotropy of MJF-printed fibre–reinforced polymer composites has not been well understood. In this work, the effect of the fibre length on the mechanical performance of MJF-printed glass fibre–reinforced polyamide 12 (GF/PA12) composites is systematically investigated. Both experimental and simulation results confirm that longer fibres are in favour of fibre alignment in the powder spreading direction. The composite parts with longer fibres exhibit higher porosity. When GFs with an average length of 226 μm are added, the ultimate tensile strength and tensile modulus of the composites measured in the powder bed spreading direction are remarkably improved by 51% and 326%, respectively, as compared with those of neat PA12 specimens. This work provides guidance for the printing of other high-strength fibre–reinforced polymer composites.